Pengembangan Integrated Learning Lab untuk Simulasi Network Function Virtualization (NFV) Menggunakan Openstack - Zulkipli, Zulkipli; Aranbi, Muhammad Defa; Putri, Lara Aulia; Purnomo, Renno; Rania, Salwa; Sauri, Sovian (Indo-MathEdu Intellectuals Journal, 2026)
The development of cloud computing-based computer network technology requires flexible, scalable, and efficient infrastructure. This challenge has an impact on computer network learning, which still relies heavily on theoretical approaches and physical laboratories with limited equipment and costs. This study aims to examine the development of an Integrated Learning Lab as a simulation-based network learning medium using Network Function Virtualization (NFV) on the OpenStack platform. The methods used are literature review and conceptual analysis of the concepts of NFV, OpenStack, and integrated learning laboratory models in the context of computer network education. The results of the study show that NFV enables network functions such as routers, firewalls, and load balancers to run virtually as Virtual Network Functions without dependence on special hardware. OpenStack acts as a Virtualized Infrastructure Manager that centrally manages computing and network resources, thereby supporting realistic NFV simulations. The discussion shows that the NFV and OpenStack-based Integrated Learning Lab has the potential to improve students' conceptual understanding and practical skills, while providing a flexible and efficient learning environment. This study concludes that the laboratory model is relevant for application in computer network learning to bridge academic needs and the demands of the modern network industry.